(untitled) (Лучшие интеллектуальные исследования, 2025)
Endometrial hyperplastic processes (EHP) rank among the most common pathologies affecting women during the perimenopausal period. The aim of this study is to emphasize the importance of early detection of endometrial hyperplasia and the assessment of its oncogenic potential, utilizing modern classification systems and diagnostic techniques. The research methodology includes a review of scientific literature and clinical case analyses. The results demonstrate that timely diagnosis and systematic follow-up significantly reduce the likelihood of malignant transformation, lower the risk of cancer development, and contribute to the overall improvement of patients’ health and quality of life.